Relation between cell-to-cell adhesion and angiogenesis and clinico-morphological prognostic factors in patients with gastric cancer - Bazas, V.M.; Lukyanova, N.Yu.; Demash, D.V.; Galakhin, K.O.; Myasoedov, D.V. (Experimental Oncology, 2008)
To study the relation between the expression of the molecules of cell-to-cell adhesion (Е-cadherin, a- and b-catenins) and vascular endothelial growth factor (VEGF) and traditional clinico-morphological characteristics of tumors to evaluate their prognostic value in the patients with gastric cancer. Methods: To analyze the expression of Е-cadherin, a- and b-catenins, and VEGF the paraffin embedded tumor samples were studied by immunohistochemical analysis with the use of respective monoclonal antibodies. Results: The presence of E-cadherin in tumors correlated with the absence of metastases in regional lymph nodes and was observed, as a rule, in the patients at the early stages of the disease. The presence of b-catenin expression has been detected in gastric tumors of the patients without distant metastases, while the level of VEGF expression correlated with the degree of gastric wall injury. It has been demonstrated that the expression of E-cadherin and a-catenin is associated with favourable disease course and is a characteristic pattern for early stages of gastric cancer of intestinal type. However, VEGF expression is typical for the late stages of gastric cancer of diffuse type and is associated with poor prognosis. Conclusion: At the base of combined clinical, histological and immunohistochemical analysis of gastric tumors it has been shown that E-cadherin, a-catenin and VEGF could be used as informative markers of the disease course. Цель: изучение связи экспрессии молекул межклеточной адгезии (Е-кадгерина, α- и β-катенина) и фактора роста
эндотелия сосудов (VEGF) с традиционными клинико-морфологическими характеристиками опухолей для определения
их прогностического значения у больных раком желудка. Методы: для определения данных белков в парафиновых
срезах тканей пациентов использовали иммуногистохимический метод с использованием моноклональных антител,
специфических к Е-кадгерину, α- и β-катенину, а также VEGF. Результаты: присутствие в карциномах Е-кадгерина
коррелировало с отсутствием метастазов в регионарных лимфатичнеских узлах и наблюдалось, как правило, у больных
на ранних стадиях болезни. Наличие экспрессии β-катенина отмечалось в карциномах желудка тех больных, которые не
имели отдаленных метастазов, а уровень экспрессии VEGF четко коррелировал со степенью поражения стенки желудка.
Показано, что экспрессия Е-кадгерина и α-катенина ассоциируется с благоприятным прогнозом и является характерным
признаком ранних стадий рака желудка кишечного типа. В то же время экспрессия VEGF характерна для поздних стадий
рака желудка диффузного типа и указывает на неблагоприятный прогноз. Выводы: в результате комплексного клинического,
гистологического и иммуногистохимического анализа рака желудка установлено, что определение Е-кадгерина, α-катенина
и VEGF может быть использовано в качестве информативных маркеров течения заболевания.